Thermally Switchable Metasurface for Controlling Transmission in the THz-gap - Kumar N.; Ghosh S.K.; Bhattacharyya S. (My University, 2025)
This paper presents a metasurface (MS) providing single to dual transmission frequency bands under different thermal excitation conditions. Vanadium dioxide (VO2) has been incorporated into a metallic MS design to generate a switching feature under temperature variations. The proposed VO2-based MS offers dual band transmission responses at 1.4 THz and 2.66 THz at room temperature (300 K). The same structure exhibits single band transmission response at 1.4 THz by rejecting the higher band, when the VO2 layer is acting as a metal under thermally heated condition (above 340 K). The device is polarization-insensitive due to four-fold symmetry and transmission performance has been found to be angularly stable up to 40° for both insulating as well as metallic phases. The device responses at two distinct states have also been verified by an equivalent circuit model. This device can find potential applications towards upcoming 6G and futuristic communication systems involving terahertz (THz) frequency band as well as shielding purposes. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.